2014
DOI: 10.1007/s00348-014-1724-6
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric intake flow measurements of an IC engine using magnetic resonance velocimetry

Abstract: Magnetic resonance velocimetry (MRV) measurements are performed in a 1:1 scale model of a singlecylinder optical engine to investigate the volumetric flow within the intake and cylinder geometry during flow induction. The model is a steady flow water analogue of the optical IC-engine with a fixed valve lift of 9:21 mm to simulate the induction flow at crank-angle 270 bTDC. This setup resembles a steady flow engine test bench configuration. MRV measurements are validated with phaseaveraged particle image veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 30 publications
1
39
0
2
Order By: Relevance
“…For conventional engines at these operating conditions, potential compressibility effects during the intake stroke are limited to very small valve lifts and are considered negligible. Freudenhammer et al [22,23] showed that the intake stroke of a water analogue and a real engine matches well in the case of similar Reynolds numbers, which also justifies the use of water for this specific investigation here. The specifications are summarized in Table 1.…”
Section: Engine Setup and Methodologysupporting
confidence: 64%
See 1 more Smart Citation
“…For conventional engines at these operating conditions, potential compressibility effects during the intake stroke are limited to very small valve lifts and are considered negligible. Freudenhammer et al [22,23] showed that the intake stroke of a water analogue and a real engine matches well in the case of similar Reynolds numbers, which also justifies the use of water for this specific investigation here. The specifications are summarized in Table 1.…”
Section: Engine Setup and Methodologysupporting
confidence: 64%
“…11a) results in a focussed flow between the angles of about −60 • and 60 • . This distribution is characteristic for these types of intake ports (see also [22,23]). For global information, the radial momentum flux through the evaluation area is integrated along the height of the valve gap.…”
Section: Tumble Generationmentioning
confidence: 78%
“…"High-speed" PIV allows time-resolved investigations of in-cylinder flow structures and their development within a single cycle, while tomographic PIV enables volumetric measurements [10]. The mean threedimensional flow in the intake port was fully quantified using Magnetic Resonance Velocimetry (MRV) by Freudenhammer et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…Other datasets relevant for engine combustion include the laboratory flames, for example, from the TNF workshop or engine-related flow bench data to characterize the intake flow. 21,110 Simulations of these systems can be performed at varying resolutions. As mentioned above, for engine combustion process design, the whole range from URANS-VLES to full-scale LES should be considered.…”
Section: 100-102mentioning
confidence: 99%